FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI - Falencia, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of liquidity, asset structure, profitability, and growth on capital structure in manufacturing industries listed in Indonesian Stock Exchange during the period of 2016-2018. This research used 73 samples of manufacturing companies that have been previously selected using purposive sampling method for three years. The data used were secondary data in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 9.0. The result of this research shows that asset structure and liquidity has an effect on capital structure, while liquidity and growth does not have an effect on capital structure. Suggestion that can be given for the future research is to use other independent variables, such as firm size.